ANALISIS MODEL TARIKAN PERJALANAN PADA KAWASAN PUSAT PEMERINTAHAN PROVINSI BANTEN (KP3B) - Budiman, Arief; Bethary, Rindu Twidi; Prativi, Hana Budi (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The purpose of this research is to determine causative factors and how strong these influence trip attraction at Banten Province Government Center. The result of this research is a mathematical model of trip attraction. The method used is multiple linear regression analysis. The model as the result of this research was obtained are as follows first: general model as Y =-0,712 + 1,931X4 + 1,801X5 – 1,014E-6X7, second: motor biker’s model as Y =-0,199 + 1,009X3 + 0,300X5 –0,176X6 + 0,010X7, third: car driver’s trip attraction model Y = -0,566 + 1,032X4 + 0,638X5 – 0,028X8 with R2 as 0,934, and last: public transportation user’s model as Y = 0,229 - 0,157X4 + 0,739X6 +0,041X8+ 0,148X9 with the variables as X4= Car Owners, X5= Car and Motorbike Owners, X6= Number Of Respondents Not Having Vehicle, X7= Number Of Respondents Choose a Faster Time, X8= Number Of Respondents Choose Distance Closer, X9= Number Of Respondents Choose Cheaper Cost.